The Effect of Project-Based Learning in Building Water Rockets on Elementary School Students’ Independent Learning and Critical Thinking - Bun Sarianto; Subuh Anggoro; Ristiana Dyah Purwandari (International Journal Labs, 2026)
The development of 21st-century skills, particularly learning independence and critical thinking, has become an important focus in elementary education. However, many elementary school students still demonstrate limited independence in managing their learning processes and underdeveloped critical thinking skills due to the dominance of conventional teacher-centered learning approaches. Project-Based Learning (PjBL) is considered an effective instructional model because it encourages students to actively construct knowledge through meaningful experiences, problem-solving activities, and real-world projects. This study aimed to examine the effect of water rocket-based Project-Based Learning on elementary school students’ learning independence and critical thinking skills. The research employed a quantitative quasi-experimental method using a Nonequivalent Control Group Design. The participants were elementary school students from the Rantasari Cluster, Ajibarang District, with data collected through observation, critical thinking tests, and documentation. Data analysis was conducted using prerequisite tests, independent-samples t-tests, and Pearson correlation analysis. The results showed that PjBL through water rocket-making activities significantly improved students’ critical thinking skills (p = 0.023 < 0.05) and learning independence (p = 0.012 < 0.05) compared with conventional learning methods. Furthermore, critical thinking skills and learning independence demonstrated a significant moderate relationship, with a correlation coefficient of 0.490. These findings indicated that water rocket-based PjBL provided meaningful learning experiences that promoted student autonomy, exploration, collaboration, and higher-order thinking skills. Therefore, PjBL can be recommended as an innovative instructional strategy to strengthen elementary students’ critical thinking and independent learning abilities.